Triptan Education and Improving Knowledge for Optimal Migraine Treatment: An Observational Study - Baron, Eric P.; Markowitz, Shira Y.; Lettich, Alyssa; Hastriter, Eric; Lovell, Brigitte; Kalidas, Kavita; Dodick, David William; Schwedt, Todd J. (Headache, 2014)
Background It is generally felt that patient education and patient knowledge regarding triptan use for acute migraine management are important for successful and safe treatment. It is unclear how knowledgeable triptan users are regarding their triptan, how much education occurs when triptans are prescribed, and the impact patient education has on actual patient knowledge regarding triptan use. Objective The primary objective was to compare triptan users' self‐perceived knowledge and actual knowledge about triptans in patients who report having received triptan education vs patients who report not having received triptan education. Methods This was a multicenter prospective observational study of 207 migraine patients who were using triptans for abortive therapy and who were being evaluated as new patients at academic headache specialty clinics in the United States. Patients completed standardized questionnaires regarding their self‐perceived knowledge about triptans, their actual knowledge regarding triptans, and the perceived education about the triptan that they had received at the time of prescription. Results Although greater than 80% of the subjects reported receiving education about when to take the triptan and the number of doses they could take for headache, only 71.5% reported receiving education about triptan side effects, 64% for the number of triptan doses they could take each week/month, 64% for taking other medications with the triptan, and 49% for medical contraindications to triptan use. Compared with subjects who did not recall receiving education about when to take their triptan, subjects who recalled such education had a statistically significant greater actual knowledge for taking the triptan immediately after a headache begins (91% vs 77%, P = .049; confidence interval [CI]: 0.00–0.33), treating when pain is mild (75% vs 50%, P = .009; CI: 0.04–0.45), understanding that they do not need to fail treatment with over‐the‐counter medications before taking a triptan (74% vs 42%, P = .001; CI: 0.11–0.51), and recognizing that coronary artery disease is a contraindication to triptan use (40% vs 19%, P = .001; CI: 0.09–0.34). Conclusion This study provides evidence that patients who recall having received education at the time of triptan prescribing have greater knowledge regarding optimal triptan use. Triptan users who recalled having received this education had greater recognition of the importance of taking the triptan immediately at the onset of a headache, treating when pain is mild, not needing to fail treatment with over‐the‐counter medications before taking a triptan, and understanding that coronary artery disease is a contraindication to triptan use.